Ensayo de evaluación. Maíz temprano y tardio en alta y baja densidad - Funaro, Daniel Oscar; Dillchneider Loza, Alexandra; Figueruelo, Andrea Mariana; Fossaceca, Donato; Sphan, Pablo; Busch, Jose Maria; Fossaceca Galizzi, Valentin (EEA Anguil, INTA, 2022)
EEA INTA Anguil